Diagnostic and therapeutic practices of cardiac sarcoidosis in the United States: a nationwide questionnaire based study - Younis, Moustafa; Abu Kar, Abdullah; Abdel Jawad, Mohammad; Al-Zamer, Yazan; Alawneh, Diala; Patel, Divya; Mehrad, Borna; Alzghoul, Bashar (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Cardiac sarcoidosis (CS) is the second most common cause of death in patients with sarcoidosis and data pertaining to its diagnosis and management is limited. We sought to describe diagnostic modalities and management of patients with CS in the United States, based on a national registry questionnaire. Methods: We conducted a retrospective study based on a national registry investigating 3,835 respondents to the Foundation for Sarcoidosis Research Questionnaire. The registry includes patient surveys completed between June 2014 and August 2019. Summary and univariate analyses were performed. Results: A total of 394 patients (10.3%) with CS were identified; 57% (n=223) were women and 81% (n=317) were white. The mean (±SD) age at diagnosis was 45 years (±13). CS was the initial presentation of sarcoidosis in 30%. Multiorgan involvement (≥3 organs) was present in 68%. Two-thirds of patients were admitted at least once to the hospital. Cardiac magnetic resonance imaging (74.4%) was the most common diagnostic modality used followed by positron emission tomography (PET) scan (59.3%) and cardiac biopsy (n=52, 13%). Most patients received corticosteroids (86%) and steroid-sparing medications (61%) including methotrexate (26%) and tumor necrosis factor (TNF) inhibitors (19%). A combined cardioverter defibrillator and pacemaker (39%) was the most common cardiac device implanted. Conclusions: The prevalence of CS in this cohort was higher than previously described. CS was a common initial presentation of sarcoidosis. The diagnosis was most likely made using cMRI. Steroids, methotrexate and infliximab are the most common medications used. Conduction abnormalities and arrhythmias often occurred.